Bali to Ban Backpacker entering The Island. Tourism Minister: It Was Just Misunderstanding! - I Komang Bayu Segara (Bali Tourism Board, 2021)
Backpackers are one of the sub-groups detached from mass tourism and seek to achieve a complete tourism experience.1 The decline in transportation costs and the growth of communication media via the internet has made backpacking trips continue to increase. Although the trend of backpacker tourism has increased over the years, their image apparently influenced the Indonesian Government’s decision, especially when Bali was preparing for tourism opening. During his visit to Bali on Friday, September 10, 2021, Coordinating Minister for Maritime Affairs and Investment Luhut Binsar Pandjaitan mentioned that the authorities would selectively screen foreign tourists who wish to visit Bali, and no backpacker would be allowed. Albeit Jodi Mahardi had clarified Luhut Binsar pandjaitan’s statement on September 14, 2021, then reaffirmed many times by the Minister of Tourism and Creative Economic and the Vice Governor of Bali, several foreign media still quoted Luhut’s initial statement. The uproar of Prohibiting Backpacker Tourists sounded around the globe and received backlash from expatriates and tourism actors in Bali. Backpacker tourists received a relatively negative image by some economic and tourism actors, but it does not mean that backpacker tourists do not contribute to a region’s economy. Some studies suggested that backpacker tourists contribute to small business development and promote tourism destinations to the world.